2019
DOI: 10.1016/j.fusengdes.2019.03.091
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the influence of the recycling coefficient on He confinement in DEMO reactor

Abstract: This work describes integrated numerical modelling applied to DEMO discharges with tungsten wall and divertor, using the COREDIV code, which self-consistently solves 1D radial transport equations of plasma and impurities in the core region and 2D multi-fluid transport in the SOL. The model is self-consistent with respect to both the effects of impurities on the α-power level and the interaction between seeded (Ar) and intrinsic impurities (tungsten, helium). This work is to analyse the influence of the helium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…This means that there is a small margin in respect to ρ * . Note that in [39] similar results were obtained for EU-DEMO1 parameters. There, the ratio ρ * varies in the range of 2.6 ÷ 7.8.…”
Section: Numerical Solutions For the Selected Tokamak-reactors Parame...supporting
confidence: 83%
“…This means that there is a small margin in respect to ρ * . Note that in [39] similar results were obtained for EU-DEMO1 parameters. There, the ratio ρ * varies in the range of 2.6 ÷ 7.8.…”
Section: Numerical Solutions For the Selected Tokamak-reactors Parame...supporting
confidence: 83%
“…The dependence of plasma current (Ip) and line averaged plasma density (<ne,line>) on R and BT are presented in Table I. In the simulations, 71.6% of the alpha power (Pα) heats the electrons and the remaining 28.4% the ions, as suggested in other papers [13,14], while the very important parameter ζ=D/χe, ratio between the particle and heat cross-field diffusion coefficients in the core is set to 0.35, as for the past COREDIV simulations [3,4,13]. Its magnitude determines the amount of the He ashes accumulation, and then that of the produced fusion power.…”
Section: Investigation With the Self-consistent Code Coredivmentioning
confidence: 72%
“…The simulations are prepared for the EU DEMO1 2018 configuration with the following main parameters: toroidal radius RT= 9.0 m, plasma radius a = 2.9 m, plasma current Ip = 17.75 MA, toroidal magnetic field BT =5.85 T, elongation -1.65, electron density <ne>VOL = 7.26×10 19 m -3 , separatrix density was kept at the 40% level of the volume average (ne sep = 0.4 <ne>VOL) and for standard case is ne sep = 2.9×10 19 m -3 , the confinement factor H-factor (IPB98(y,2) [16]) was equal to H98 = 1.1 whereas the auxiliary heating power was set to Paux =50 MW. In our simulation, we have assumed that 28.4% of alpha power (Pα) is transfer to ions and remaining 71.6% to the electrons [18].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In Ref. [16], we shown that the helium recycling coefficient has strong influence on the He confinement time. The He confinement increases linearly from 7.25 s to 26.9 s for RHe values going from lowest to highest recycling coefficient.The burn-up fraction in our model is defined as: fbr = 2Γα/Γful, where Γα is α-particle source and Γful is the fueling source.…”
Section: Modelmentioning
confidence: 98%